Japanese physicians' experiences of terminally ill patients voluntarily stopping eating and drinking: a national survey. Issue 2 (8th November 2017) - Shinjo, Takuya; Morita, Tatsuya; Kiuchi, Daisuke; Ikenaga, Masayuki; Abo, Hirofumi; Maeda, Sayaka; Tsuneto, Satoru; Kizawa, Yoshiyuki
Abstract : Objectives: Voluntarily stopping eating and drinking (VSED) could be regarded as a patients' own non-treatment decision that hastens death, which involves patients voluntarily forgoing food and liquid until death. The aims of this study were to investigate the experience of home hospice physicians and palliative care specialists who care for patients during VSED in Japan, and their opinions on continuous deep sedation (CDS) as a means to relieve patient symptoms during VSED. Methods: 219 home hospice physicians and 695 palliative care specialists across Japan were surveyed by mail questionnaire in 2016. Results: A total of 571 (62%) responses were analysed. A total of 185 (32%) had experience of patients who selected VSED. In response to questions about CDS to provide relief to patients during VSED, the number of physicians who replied that CDS was acceptable was 88 (15%). Conclusions: In Japan, 32% of physicians surveyed replied that they had experience of caring for patients during VSED in a clinical setting and 15% considered CDS acceptable.